Penerapan Metode Time Series Analysis pada Sistem Informasi Posyandu untuk Mengetahui Pola Berat Badan Anak menggunakan Whatsapp Gateway - Helmi, Elsy Shafira; Triase, Triase (Journal of Information System Research (JOSH), 2024)
Posyandu Melati Batang Gasan has been routinely collecting children's weight data every month, but is facing difficulties in managing and analyzing the data effectively. Data recording is only done in books without in-depth analysis, causing delays in proactive actions towards abnormal child growth. This manual recording is time-consuming, prone to errors, and hinders more in-depth analysis. In addition, information regarding the schedule of posyandu activities is often received late by parents, resulting in low community participation. The purpose of this research is to build a Posyandu Information System using the Time Series Analysis method and integrate the Whatsapp Gateway feature to manage children's weight data, perform time series analysis, and send Whatsapp notifications. Based on the existing problems, this research implements the Posyandu Information System using the Time Series Analysis method with Double Exponential Smoothing to monitor and forecast children's weight development, and integrates the Whatsapp Gateway feature to enhance communication and parental participation. The research results show good accuracy, with the forecasted weight and height of children for August being 14.6 and 104.6, respectively, with a Mean Absolute Percentage Error (MAPE) of 2%, and WhatsApp Gateway notifications can be sent through the system. Overall, this method is effective in predicting children's weight with good accuracy and increasing parental attendance at the posyandu.